Advanced Gastric Cancer in a Young Patient - Ryan Ranitya; Ari Fahrial Syam; Murdani Abdullah; Marcellus Simadibrata; Vera Yuwono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Gastric cancer remains the second most common cancer in the world, and is usually found in men, especially those over 50 years of age. The diagnosis is made by endoscopic biopsy. The high frequency of late diagnosis or advanced stages accounts for the overall poor prognosis for this tumor. Surgery is the most frequently employed modality for both cure and palliation. However, most patients present with advanced disease that is incurable. We reported a rare case of young female patient aged 23 years old with advanced gastric carcinoma. The main clinical features were epigastric discomfort, vomiting, and weight loss. An abdominal mass was palpable on physical examination. Endoscopy showed a giant tumor mass causing gastric outlet obstruction, nodular lesion, ulcerative and hemorrhagic. The histopathologic examination revealed mucinous gastric carcinoma. Palliative resection could not be performed because the tumor tightly adhered to adjacent structures. Jejunostomy was performed to allow enteral nutrition. Best supportive care is very important to improve the quality of life. Keywords: Gastric cancer, young patient